Are Economics Learning Outcomes Influenced by Learning Motivation and Active Learning? (Buana Pendidikan: Jurnal Fakultas Keguruan dan Ilmu Pendidikan Unipa Surabaya, 2022)
Education aims to educate students to become human beings who are knowledgeable, creative, independent, capable, noble and responsible, these goals can be achieved with learning motivation and active learning in learning so that the learning outcomes obtained are good, especially in economic subjects. The purpose of this study was to determine 1) the partial effect of learning motivation variables on economic learning outcomes, 2) the effect of learning activities on economic learning outcomes, 3) the simultaneous influence of learning motivation variables and learning activities on economic learning outcomes in class X IPS SMAN 1 Cerme. The sampling method used was purposive sampling so that a sample of 86 students was obtained. This study uses primary data obtained from questionnaires. The results of this study indicate that there is a partially significant positive effect between learning motivation on economic learning outcomes, and there is a significant positive influence on learning activity variables on learning outcomes variables. Also simultaneously there is a significant positive effect between learning motivation and learning activity on economic learning outcomes and with an Adjusted R-squared value of 0.380 the contribution of the independent variable is 38%